2018
DOI: 10.3389/fcimb.2018.00241
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Notch Signaling and STAT3 in TLR-Activated Human Primary Monocytes

Abstract: The highly conserved Notch signaling pathway essentially participates in immunity through regulation of developmental processes and immune cell activity. In the adaptive immune system, the impact of the Notch cascade in T and B differentiation is well studied. In contrast, the function, and regulation of Notch signaling in the myeloid lineage during infection is poorly understood. Here we show that TLR signaling, triggered through LPS stimulation or in vitro infection with various Gram-negative and -positive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…Consistently, in gram-positive and gram-negative bacterial infection models, IL-6 was noted to induce the expression of DLL-1 in primary human monocytes through activation of transcription factor STAT-3. In turn, DLL-1 was shown to enhance IL-6 production and subsequently activate STAT-3 [46]. Of course, Notch signaling seems to directly regulate IL-6 expression.…”
Section: Reciprocal Modulation Of Notch Signaling and Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, in gram-positive and gram-negative bacterial infection models, IL-6 was noted to induce the expression of DLL-1 in primary human monocytes through activation of transcription factor STAT-3. In turn, DLL-1 was shown to enhance IL-6 production and subsequently activate STAT-3 [46]. Of course, Notch signaling seems to directly regulate IL-6 expression.…”
Section: Reciprocal Modulation Of Notch Signaling and Cytokinesmentioning
confidence: 99%
“…Specifically, lipopolysaccharide (LPS) in gram-negative bacteria binds to TLR-4, which in turn mediates expression of pro-inflammatory mediators through NF-κB and microtubule-associated protein (MAP) kinase signaling. The mediators through autocrine and paracrine processes activate downstream signaling pathways such as Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway, which ultimately induce more modulation of the immune response [46]. Dysregulation in PRRs signaling system has been linked to increasing the susceptibility to various bacterial and viral infections [47,48] and the development of inflammatory and autoimmune diseases.…”
Section: Notch Signaling In Macrophagesmentioning
confidence: 99%
“…In macrophages, Notch1 directly binds to interleukin (IL)-6 promoter in response to interferon (IFN)-γ and positively regulates IL-6 production [52]. It is important to underline that IL-6, in turn, increases the expression of the Notch ligand Dll1, thus amplifying the Notch signalling and establishing a positive feedback loop that promotes the further production of IL-6 [21]. In Th cells, Notch signalling triggered by Dll1,4 ligands promotes the production of inflammatory Th1/Th17 cytokines, whereas Jagged1 suppresses IL-6-induced Th17 activation [49] (Fig.…”
Section: Notch and The "Cytokine Storm"mentioning
confidence: 99%
“…28 Likewise, PD-L1 was upregulated through a notch in human primary monocytes. 29 In this study, we showed for the first time that Notch signaling pathway is critical for PD-L1 expression on breast CSCs.…”
Section: Discussionmentioning
confidence: 73%